Conflict, cooperation and change: the political economy of trade and trade policy - Michie, J; Kitson, M (Routledge, 1995)
Domestic and international economic policy is still dominated by laissez-faire economics, despite the failure of such policy analysis in the 1980s to have brought about the sort of economic growth and high employment witnessed through the 1950s and 1960s. The dominant feature of international trade theory is the assumed superiority of free trade and non-intervention. In this paper we argue that the neo-classical case for free trade is based on inappropriate assumptions; relax these assumptions and the case for non-intervention goes with them. This paper argues that to return to a situation of reasonable stability and balanced growth for individual countries, and for the world economy as a whole, increased management of the international trading and monetary systems will be required.